1999
DOI: 10.1177/107110079902000209
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of the Rearfoot Angle: Preliminary Values in 150 Children

Abstract: The degree of valgus in the heel during weightbearing (the rearfoot angle) is commonly used as an angular criterion in the evaluation and treatment of flatfoot in children and adults. The rearfoot angle has been frequently reported to reduce with age to a vertical heel position attained at approximately 7 years old. The present study evaluated the rearfoot angle in 150 healthy children (age range, 6-16 years). The average rearfoot angle for all children in this study was 4 degrees of valgus (SD, 1.1 degrees; r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
5

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 25 publications
(44 reference statements)
2
32
0
5
Order By: Relevance
“…The group of nonwearers had a mean angle of 9.45º, and the group of wearers, a mean angle of 2.76º. Such findings are similar to those reported by other researchers, who found values ranging from 0º to 7º valgus in children aged six to 16 years 27 , and from 5º to 7º in children aged seven to eight years 26 . There is a physiological valgus in the barefoot condition for the ankle posture of children and adolescents.…”
Section: Foot Posture and Plantar Arch Among High-heel Wearerssupporting
confidence: 81%
“…The group of nonwearers had a mean angle of 9.45º, and the group of wearers, a mean angle of 2.76º. Such findings are similar to those reported by other researchers, who found values ranging from 0º to 7º valgus in children aged six to 16 years 27 , and from 5º to 7º in children aged seven to eight years 26 . There is a physiological valgus in the barefoot condition for the ankle posture of children and adolescents.…”
Section: Foot Posture and Plantar Arch Among High-heel Wearerssupporting
confidence: 81%
“…Of more interest was the rather broad range of values detected and the finding that mean values for left and right rearfoot angles frequently surpassed the arbitrary excessive limit of 5°t o 6°regardless of group membership. While Sobel and colleagues 39 have suggested that normal rearfoot measures fall in the range of 0°to 9°and that there is a need to reconsider what might be considered an ideal normal value, their upper limit of 9°± 2°, was clearly exceeded in 36 of the 100 (36%) asymptomatic limbs examined in this study. The same limit was surpassed in approximately 20 of the 39 (51%) symptomatic limbs studied.…”
Section: Discussionmentioning
confidence: 89%
“…6,40 Orthotic intervention has been efficacious in reducing overuse symptoms, 13,15 yet some are sceptical as to whether this reduced symptomology is truly a product of skeletal realignment. Sobel and colleagues 39 have stated that early assertions of the weight-bearing neutral rearfoot angle of 0°as normal 17,28 are not supported by empirical data, and suggest 4.0°± 1.1°(range, 0°-9°) valgus orientation of the rearfoot as more descriptive of typical positioning. Similarly, others 20 have suggested that there is no evidence to support that the placement of the rearfoot in a neutral position is advantageous.…”
mentioning
confidence: 99%
“…These findings are consistent with previous studies that report no sex differences in tibial torsion, 57 navicular drop, 6,24,51,81 or standing rearfoot angle. 5,75 The lack of evidence to support a sex difference in these variables suggests that these variables alone do not independently explain the greater risk of knee injuries in females. 24,45 The interaction of a sex difference with other alignment variables that differ between males and females may more accurately identify those at increased risk of injury.…”
Section: Tibial Torsion and Subtalar Joint Pronationmentioning
confidence: 99%